Temperature Control System Using Mobile Application Interface (European Journal of Formal Sciences and Engineering, 2022)
Temperature control becomes increasingly necessary with each day, be it in industrial, commercial or residential environments. In a similar way, technology has become a common tool in everyday life. Thus, the technologies need to accompany advances in the controls of processes in many fields, creating applications that can be used in mobile devices alongside these processes. Therefore, this paper proposes temperature monitoring of an environment, via Bluetooth wireless communication and with interface display on a mobile application, developed in MIT App Inventor. While implementing commands via hardware and software a procedure to lower room temperature was applied through a ventilation system. The data are collected through a DHT11 temperature sensor, and the wireless communication is through a HC-05 Bluetooth module, both connected to the development board Arduino. It was possible to condition the cooler to work accordingly with a preset temperature range by using its IDE (Integrated Development Environment). Thereby, this project is a low-cost and advantageous alternative to temperature control and monitoring supported by technological advancements.
Keywords: temperature control, temperature sensor, innovation, mobile application, development boards, wireless communication.